Pore Habit of Gas in Gassy Sediments. Issue 5 (21st May 2021) - Terzariol, Marco; Sultan, Nabil; Apprioual, Ronan; Garziglia, Sebastien
Abstract: Gas bubbles are widespread in seafloors and lakebeds and typically found in shallow and fine‐grained sediments. Sediment properties control gas nucleation and gas migration. Gas migration and pathways have been studied mostly in clean coarse particles or fine‐grained matrices. Nevertheless, both cases show very distinct geo‐behaviors. Pore habit is defined by the counteracting effects of effective stress and pore‐throat‐dependent capillary pressure. In this article, we explore gas nucleation by CO2 gas exsolution and its consequent gas‐driven fractures (open‐mode discontinuities) or pore invasion in binary sediments as a function of fines content (FC). We conducted physical test analogies for different FC subjected to gas exsolution. Our results highlight that the pore habit of gas in gassy sediments depends on its capability to invade a neighboring pore (capillarity) and burial depth (effective stress). We show that the load dominant fraction in binary soils can be used to estimate the dominant pore throat size. We then proposed a robust methodology to predict the pore habit of gassy sediments from its properties as defined in recent developments in soil behavior and characterization. Finally, we applied it to a real case offshore Vancouver Island. Key Points: Fines content determines the global behavior of gassy and non‐gassy sediments The pore habit in gassy sediments depends on its capability to invade a neighboring pore (capillarity) and burial depth (effective stress) The analysis proposed helps understand subsurface gas activity in natural marine environments, potential passageways and stagnant bubbles